Development of standard definitions and grading for Maternal and Fetal Adverse Event Terminology. (12th October 2021) - Spencer, Rebecca N.; Hecher, Kurt; Norman, Gill; Marsal, Karel; Deprest, Jan; Flake, Alan; Figueras, Francesc; Lees, Christoph; Thornton, Steve; Beach, Kathleen; Powell, Marcy; Crispi, Fatima; et al.
Abstract: Objective: Adverse event (AE) monitoring is central to assessing therapeutic safety. The lack of a comprehensive framework to define and grade maternal and fetal AEs in pregnancy trials severely limits understanding risks in pregnant women. We created AE terminology to improve safety monitoring for developing pregnancy drugs, devices and interventions. Method: Existing severity grading for pregnant AEs and definitions/indicators of 'severe' and 'life‐threatening' conditions relevant to maternal and fetal clinical trials were identified through a literature search. An international multidisciplinary group identified and filled gaps in definitions and severity grading using Medical Dictionary for Regulatory Activities (MedDRA) terms and severity grading criteria based on Common Terminology Criteria for Adverse Event (CTCAE) generic structure. The draft criteria underwent two rounds of a modified Delphi process with international fetal therapy, obstetric, neonatal, industry experts, patients and patient representatives. Results: Fetal AEs were defined as being diagnosable in utero with potential to harm the fetus, and were integrated into MedDRA. AE severity was graded independently for the pregnant woman and her fetus. Maternal ( n  = 12) and fetal ( n  = 19) AE definitions and severity grading criteria were developed and ratified by consensus. Conclusions: This Maternal and Fetal AE Terminology version 1.0 allows systematic consistent AE assessment in pregnancy trials to improve safety. Key points: What's already known about this topic? Adverse event (AE) monitoring is central to assessing therapeutic safety. The lack of a comprehensive AE framework in pregnancy trials severely limits understanding risks in pregnant women What does this study add? Through international consensus we systematically developed definitions and severity grading for maternal and foetal AEs: Maternal and Fetal AE Terminology Version 1.0. New fetal AE definitions were adopted by the Medical Dictionary for Regulatory Activities. This terminology should be used to monitor safety in pregnancy trials